Bio-Efficacy of Chrysoeriol7, a Natural Chemical and Repellent, against Brown Planthopper in Rice - Kim, Eun-Gyeong; Yun, Sopheap; Park, Jae-Ryoung; Jang, Yoon-Hee; Farooq, Muhammad; Yun, Byoung-Ju; Kim, Kyung-Min (International Journal of Molecular Sciences, 2022)
Brown planthopper (BPH, Nilaparvata lugens Stal.) is the most damaging rice pest affecting stable rice yields worldwide. Currently, methods for controlling BPH include breeding a BPH-resistant cultivar and using synthetic pesticides. Nevertheless, the continuous cultivation of resistant cultivars allows for the emergence of various resistant races, and the use of synthetic pesticides can induce environmental pollution as well as the emergence of unpredictable new pest species. As plants cannot migrate to other locations on their own to combat various stresses, the production of secondary metabolites allows plants to protect themselves from stress and tolerate their reproduction. Pesticides using natural products are currently being developed to prevent environmental pollution and ecosystem disturbance caused by synthetic pesticides. In this study, after BPH infection in rice, chrysoeriol7 (C7), a secondary metabolite that induces resistance against BPH, was assessed. After C7 treatment and BPH infection, relative expression levels of the flavonoid-related genes were elevated, suggesting that in plants subjected to BPH, compounds related to flavonoids, among the secondary metabolites, play an important role in inducing resistance. The plant-derived natural compound chrysoeriol7 can potentially thus be used to develop environmentally friendly pesticides. The suggested control of BPH can be effectively used to alleviate concerns regarding environmental pollution and to construct a relatively safe rice breeding environment.